AB0258 Persistence of Extensive MRI Osteitis Associates RAPID Radiographic Progression with Predominant Loss of Joint SPACE Narrowing and Hand Grip in Patients with Rheumatoid Arthritis Inadequate Response to Methotrexate. (10th June 2014) - Katayama, K.; Okubo, T.; Sato, T.; Fukai, R.; Abe, S.; Ito, H.; Kamishima, T.
Abstract : Background: Magnetic resonance imaging (MRI) osteitis has been reported to be a strong independent predictor of radiographic joint damage (RJD) in rheumatoid arthritis (RA) (1). We reported continuation of MRI osteitis, especially extensive osteitis is prognostic factor for rapid radiographic progression (RRP) in Adalimumab + methotrexate (MTX) combination therapy (2). However, little has been known about the relationship between MRI osteitis and RRP. Moreover, there was no information about progression pattern of RRP. Objectives: To investigate the association of extensive MRI osteitis and RRP and to clarify RRP progression pattern. Methods: We retrospectively compared the clinical and imaging data at the first visit (mean 8.2 months after onset, ) and after MTX therapy (average dose; 8.3mg/week, mean 19.5 months after onset) between one hand with extensive osteitis (osteitis (+)) and another hand with little or no osteitis (osteitis (−)) in 12 RA patients. Gd-enhanced MRI (0.3T) of both hands were evaluated by the Rheumatoid Arthritis Magnetic Resonance Imaging Score (RAMRIS). Joint erosion (JE) and joint space narrowing (JSN) score in both hands and feet by the conventional radiography (CR) were also evaluated by the modified total sharp score (m-TSS). Bone mineral density (BMD) in both hands was measured by the DEXA (PRODIGY, en CORE, version. 11.4). Hand grip (HG) in both hands was measured by the hand dynamometer (max 300mm Hg) before blood examination. Wilcoxon's rank sum test was used to compare continuous data. Results: The ΔmTSS/year and the percentages of the RRP in the first visit (baseline) or after the MTX therapy (about 1year later) were 43.1 and 91.6%, 20.3 and 91.6%, respectively.At the first visit, extensive osteitis (p<0.001) and synovitis (p<0.01), JE score in CR (P<0.01) were significantly increased in hands with osteitis (+) compared with hands in osteitis (−). The severe loss of hand grip (less than 50% of osteitis (−) hands) was observed (p<0.01). About 1 year later, JSN in CR (p<0.01) and loss of HG (p=0.06) were increasing in hands in osteitis (+) with continuation of the extensive osteitis (p<0.05) and synovitis (p<0.05), JE in CR (p<0.01), prominent loss of HG (p<0.01) compared with hands in osteitis (−). As shown in table, in osteitis (+) hands, JSN in CR significantly increased during MTX thrapy (P<0.01) but JE did not increased (P=0.25). In osteitis (−) hands, JSN and JR in CR did not increased during MTX thrapy. Conclusions: Extensive osteitis is highly associated with RRP. Continuation of MRI osteitis and synovitis, severe loss (less than 50%) of HG with progressive loss of JSN is characteristic. References: Colebatch AN et al. Ann Rheum Dis 2013;72:804-814 Katayama K et al. Eular meeting 2012, SAT100 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4181